Zoning for risk of methane gas explosions in coal mining in Boyacá, Colombia - Arteaga Hernández, Juan Sebastián (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
In Boyacá, the number of deaths from methane explosions in coalmines constitutes the greatest mining risk, and the victims can be around 10 deaths per year. Therefore, the province was zoning to determine the mining areas with the highest risk from the measurements of methane concentrations on the mining fronts. From the database of the National Mining Office, the methane gas contents reported in percentage during the inspection visits were reviewed. This information was organized and tabulated in a GIS platform, then filtered to use the most useful data. This review shows that the area of greatest risk is between Tasco and Socotá, where the highest gas contents have also been reported in desorption tests; based on that, this area requires more attention and care during follow-up visits in order to avoid accidents.